2016
DOI: 10.4338/aci-2015-12-r-0174
|View full text |Cite
|
Sign up to set email alerts
|

The Chief Clinical Informatics Officer (CCIO)

Abstract: A better defined and specified education and skillset for all CCIO positions will motivate the CCIO workforce and empower them to perform the job of a 21st century CCIO. Formally educated and trained CCIOs will provide a competitive advantage to their respective enterprise by fully utilizing the power of Informatics science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…However, this educational issue concerns all other healthcare stakeholders as we will need to ensure, on the one hand, the proper education and training of experts in clinical bioinformatics and, on the other, the familiarization of all concerned medical stakeholders (MDs, nurses, technologists, lab technicians, pharmacists, and other medical or clinical staff) with this specialty. Or, as stated elsewhere, “future education and training must reflect the changing body of knowledge and must be guided by changing day-to-day informatics challenges” [102]. The days when a single physician (or even hospitalist) could cover the entire gamut of medicine are gone, as the practice of medicine becomes increasingly multidisciplinary.…”
Section: Challenges Of Evidence-based Precision Medicinementioning
confidence: 99%
“…However, this educational issue concerns all other healthcare stakeholders as we will need to ensure, on the one hand, the proper education and training of experts in clinical bioinformatics and, on the other, the familiarization of all concerned medical stakeholders (MDs, nurses, technologists, lab technicians, pharmacists, and other medical or clinical staff) with this specialty. Or, as stated elsewhere, “future education and training must reflect the changing body of knowledge and must be guided by changing day-to-day informatics challenges” [102]. The days when a single physician (or even hospitalist) could cover the entire gamut of medicine are gone, as the practice of medicine becomes increasingly multidisciplinary.…”
Section: Challenges Of Evidence-based Precision Medicinementioning
confidence: 99%
“…Currently, NI are suggested to be core competencies instead of an isolated set of skills in nursing (Abdrbo 2015;Kleib and Nagle 2018;Sipes et al 2017). Informatics competency requirements are set for different roles and all levels of nurses (nurse administrators, nurse researchers, nurse teachers and practicing nurses) (Collins et al 2017;Egbert et al 2018;Grobe 1989;Kannry et al 2016;Skiba 2016;Strudwick et al 2019) and across different levels in health systems, ranging from service providers to national-level strategic decision makers (Whittaker et al 2015). However, a systematic and formal approach to the implementation of NI in nursing education is still lacking in some countries (Cummings et al 2015;Egbert et al 2018), and research has shown that graduate nurses are inadequately prepared in NI when entering practice (Shin et al 2018) and that more NI training is needed at postgraduate levels in nursing (Choi et al 2013;Kupferschmid et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, clinical informatics leadership roles, i.e. Chief Clinical Informatics Officer, and Chief Nursing Informatics Officer, should be clearly defined and integrated into the organizational structure of the healthcare institution (Kannry et al, 2016). Academic institutions should also prepare to meet the demand for these roles and integrate health information management and informatics training into F o r P e e r R e v i e w the academic curriculum for all health and allied-health disciplines (Cooper, 2009).…”
Section: Discussionmentioning
confidence: 99%